Simulasi absorpsi multikomponen gas dalam larutan K2CO3 dengan promoter MDEA pada packed column - Ningsih, Erlinda; Pudjiastuti, Lily; Wulansari, Dessy; Anggraheny, Nurul; Altway, Ali; Budhikarjono, Kuswandi Kusno (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2012)
Simulation of multi-component gas absorption in the K2CO3 solution with promoter MDEA in packed column This research aims to study theoretically the performance of packed column to absorb CO2 and H2S from acid gas using MDEA promoted K2CO3 solution by considering solubility of other gases. Performance is expressed as CO2 recovery percentage. Research was carried out by developing simulation program of gases absorption with chemical reaction in packed column under isotherm condition. Prediction results were validated with petrochemical plant data. The simulation program can predict concentration distribution of dissolved gases and reactants in liquid phase at packed column and also the percentage of CO2 and H2S recovery. Results show that CO2 and H2S recovery increase with the increasing pressure and liquid flow rate. The study also depicts presence of an optimum temperature where CO2 recovery increases with increasing temperature below optimum temperature and decrease with increasing temperature above optimum temperature. The absorption rate increase or decrease with increasing temperature depending on relative effect of temperature on reaction rate, gas diffusivity and solubility. For CO2 absorption into MDEA promoted 30% K2CO3 solution at packed column 3 m in diameter, and 30 m in height filled with 7 cm IMPT packing, the highest CO2 removal efficiency is 99.947% on 100 oC, 32 atm, liquid flow rate of 5900 m3/hr, and gas flow rate of 308 kNm3/hr. Keywords: reactive absorption, isothermal, multi-component, promoter, two-film modelAbstrakPenelitian ini bertujuan untuk mempelajari secara teoritis kinerja packed column untuk absorpsi CO2 dan H2S dari gas asam dengan larutan K2CO3 dan promotor MDEA dengan memperhatikan kelarutan gas-gas yang lain, yang dinyatakan dengan %-recovery CO2. Penelitian ini dilaksanakan dengan membuat program simulasi untuk absorpsi gas CO2 disertai reaksi kimia dalam kondisi isothermal. Hasil prediksi simulasi ini divalidasi dengan data lapangan. Dengan menggunakan model packed column ini, diperoleh distribusi konsentrasi gas-gas terlarut, distribusi konsentrasi reaktan dalam fasa cair dalam kolom absorber dan prediksi %-recovery CO2 dan H2S. Hasil penelitian menunjukkan bahwa semakin tinggi tekanan dan laju alir absorben %-penghilangan CO2 dan H2S semakin besar. Hasil penelitian menunjukkan adanya suhu optimum. Di bawah suhu optimum kenaikan suhu menyebabkan kenaikan %-penghilangan sedangkan di atas suhu optimum kenaikan suhu menurunkan %-penghilangan. Laju absorpsi meningkat tergantung pada pengaruh relatif temperatur pada konstanta kecepatan reaksi, difusivitas dan kelarutan gas yang terserap. Untuk absorpsi gas CO2 kedalam larutan K2CO3 30% dengan promotor MDEA pada packed column dengan diameter 3 m dan tinggi 30 m yang diisi dengan packing IMPT 7 cm diperoleh penghilangan CO2 tertinggi 99,947% pada kondisi laju alir larutan 5900 m3/jam, temperatur 100 oC, laju alir gas 308 kNm3/jam serta tekanan 32 atm.Kata kunci: absorpsi reaktif, isothermal, multikomponen, promoter, model dua film.